Clinical Experience with Tixocortol Pivalate - Stephen B. Hanauer (Canadian Journal of Gastroenterology)
Tixocortol pivalate, the 21-thiol derivative of hydrocortisone. is a newly synthesized steroid with topical anti-inflammatory properties but is devoid of systemic glucocorticoid and mineralocorticoid activities and toxicity. The mechanism of action appears to be similar to that of other corticosteroids with regard to steroid binding sites and prostaglandin biosynthesis, however. the disassociation between local and systemic effects is due to a 'first pass' liver metabolism and rapid transformation with in red blood cells. ln both open and controlled studies in patients with acute or recurrent distal colitis, clinical efficacy has been noted at doses of 250 mg to 1000 mg in 100 ml solution without an effect on scrum cortisol levels or blood chemistries. Tixocortol pivalate has consistently shown to be as effective as systemically absorbed steroids for the treatment of distal ulcerative colitis with out the undesirable effects associated with currently available steroid preparations.